CHANGE IN QUALITY OF CHERRY FRUITS PRE-PROCESSED WITH POLYSACCHARIDE COMPOSITIONS DURING STORAGE - Vasylyshyna, O. V. (Scientific Progress & Innovations, 2020)
The effect of treatment with carrageenan solution on physical and chemical quality indicators of cherry berries during storage has been shown in the article. Alpha and Pamiat Artemenka cherry berry varieties were taken for study. Untreated berries were taken as control. Others were coated with a solution containing carrageenan and glycerin. Cherry berries were dipped in the solution, kept for 1-2 minutes, removed, drained and dried with a stream of air from ventilator. Then berries were placed in boxes and stored at a temperature of 1.0±0.5 °C, at relative air humidity of 95.0±1.0 %. According to the results of studies, the weight loss of berries of Alpha and Pamiat Artemenka cherry varieties, treated with carrageenan solution, after 15 days of storage was by 40.0−35.7 % less as compared with the control variant. When treated with 2.0 % carrageenan solution, the indices were by 45.2−42.9 % lower. After 28 days of storing berries treated with carrageenan solution, the weight loss was 22.6−35.7 % and 29.0−42.9 %., respectively. Untreated cherry berries’ firmness decreased by 41.0–45.5 % during storage. In cherry berries treated with 1% carrageenan solution, its losses were 18.8–31.1 %, and with 2.0 % solution – 15.2–17.1 %. After storage, light transmission coefficient in treated cherry berries of Alpha and Pamiat Artemenka varieties decreased slightly – by 2.7 and 8.6 %, as compared with untreated berries. At changing firmness and color, the content of dry soluble substances in cherry berries of Alpha and Pamiat Artemenka varieties decreased by 8.9−10.6 %. On the 15th day after treatment with 1 % and 2 % carrageenan solution, the losses were 5.5–6.8% and 4.9–5.5 %, respectively. After 28 days, the loss of their content was higher – by 6.2−7.4 %. Dry soluble substances were lost less at treating fruits with 2.0% carrageenan solution – 5.5–6.2 %. Thus, cherry berries treated with carrageenan solution had a longer shelf life. Weight loss was by 29.0–42.9 % lower as compared with untreated berries. When treating berries with carrageenan solution, their firmness and brilliance were preserved. Therefore, it is promising to continue research in this area for the storage of cherry berries treated with carrageenan solution.